Impaired verbal self-monitoring in individuals at high risk of psychosis. - Johns, L; Allen, P; Valli, I; Winton-Brown, T; Broome, M; Woolley, J; Tabraham, P; Day, F; Howes, O; Wykes, T; McGuire, P (2010)
BACKGROUND: Cognitive models suggest that auditory verbal hallucinations arise through defective self-monitoring and the external attribution of inner speech. We used a paradigm that engages verbal self-monitoring (VSM) to examine whether this process is impaired in people experiencing prodromal symptoms, who have a very high risk of developing psychosis. METHOD: We tested 31 individuals with an At-Risk Mental State (ARMS) and 31 healthy volunteers. Participants read single adjectives aloud while the source and pitch of the online auditory verbal feedback was manipulated, then immediately identified the source of the speech they heard (Self/Other/Unsure). Response choice and reaction time were recorded. RESULTS: When reading aloud with distorted feedback of their own voice, ARMS participants made more errors than controls (misidentifications and unsure responses). ARMS participants misidentified the source of their speech as 'Other' when the level of acoustic distortion was severe, and misidentification errors were inversely related to reaction times. CONCLUSIONS: Impaired VSM is evident in people with an ARMS, although the deficit seems to be less marked than in patients with schizophrenia. Follow-up of these participants may clarify the extent to which the severity of this impairment predicts the subsequent onset of psychosis and development of positive symptoms.